Determination of filtration area parameters under conditions of intermittent water withdrawal - I. A. Sharov; N. V. Fisun (Известия высших учебных заведений: Геология и разведка, 2025)
Background. Specific features of conducting experimental filtration works in complicated hydrogeological conditions of intermittent water withdrawal are considered. The works were carried out at the Ergeninsky mineral water deposit, situated in the area of the junction of the Ergeninsky upland and the Volga River valley. Conclusions about the specific features of determining the aquifer parameters under these conditions are drawn; a review of the methods used for processing such pumps is provided.Aim. Correction of the methodology of experimental filtration works under changing flow rate conditions.Materials and methods. The groundwater reserves of the Ergeninsky mineral water deposit were revised based on the experience of geological exploration at the existing site of water withdrawal. In accordance with the technological scheme, the development of the deposit was planned in the mode of intermittent withdrawal. An experimental pumping from a weakly pressurized Ergeninsky horizon was carried out for three days in the operation mode, during which 10 stages of flow rate were identified. The determination of water transmissivity coefficient was performed by the method of superposition according to the flow rate steps as a single abrupt disturbance traced by the given decrease in the given time. The level of groundwater was recorded by a pressure sensor, while the flow rate was recorded by a water meter. Pumping treatment was carried out by the method of temporary tracing. A single water intake was used. The data obtained were processed using the Microsoft Excel software.Results. The influence of periods of incomplete restoration of the groundwater level on the reliability of calculations of the transmissivity coefficient by the method of intermittent water flow rate was investigated. The conclusion is formulated about the possible causes of significant fluctuations in the water transmissivity coefficient when processing experimental filtration data, as well as about the possibility of using this method when processing such data.Conclusion. An assumption is made about the influence of the filtration area boundary of the third kind on the data obtained during experimental filtration works. This correlation is expressed by the influence of the trend (increasing or decreasing) in the change of water withdrawal on the results of calculating the water transmissivity of the Ergeninsky aquifer by the method of intermittent water withdrawal, which makes it unacceptable in these conditions. At the pumping stage with a high flow rate, the discharge inversion into the overlying horizon occurs, the results of which continue further with a drop in flow rate and is expressed by an increase in the level, rather than by its decrease, as expected.